PENGEMBANGAN MEDIA PEMBELAJARAN PECAHAN SENILAI MELALUI PERMAINAN JELAJAH HARTA KARUN BERBASIS TEACHING AT THE RIGHT LEVEL (TARL) SEKOLAH DASAR - Meli Haryanti; Fakhirah, Hanifah; Nur Afiqoh Aprilia; Dewi Rahmawati; Dian Lestari Yuningrum; Ahmad Syarif; Eko Kuntarto; Destrinelli; Hendra Sofyan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a Treasure Hunt-based learning media using the Teaching at the Right Level (TaRL) approach on equivalent fractions material in elementary school and to determine its feasibility in the learning process. This research employed a Research and Development (R&D) method using the Borg and Gall development model, which was simplified into seven stages: research and data collection, planning, initial product development, design validation, product revision, small-scale trial, and final product revision. The research subjects were students of SDN 57/IX Tangkit with diverse ability levels. Data collection techniques included expert validation questionnaires, teacher response questionnaires, and student response questionnaires. The results showed that the TaRL-based Treasure Hunt learning media is feasible for use in the learning process. The implementation of this media was able to improve students’ activeness, motivation, and understanding of equivalent fraction concepts. In addition, the TaRL approach helps students learn according to their respective ability levels, making the learning process more effective, engaging, and meaningful.